Synthesis, Spectral Identification, Thermal Studies, Antioxidant Properties, and Biological Effects for Some Metal Ion Complexes with New Schiff Base Ligand - Al-Ameer, Aseel Hikmat Abad; Shaalan, Naser (Universitas Gadjah Mada, 2025)
The tetradentate N2O2 Schiff base ligand, which is produced via the condensation reaction of 2-hydroxynaphthaldehyde with phthalohydrazide, is prepared in this work with a fair yield. The prepared ligand was characterized using a microanalysis technique (C.H.N), UV-vis, FTIR, 1H-,13C-NMR, mass spectrometry, and thermal gravimetric analysis (TGA). New complexes were synthesized by a reaction between ligand (N'1E,N'2Z)-N'1,N'2-bis((1-hydroxynaphthalen-2yl)methylene)phthalohydrazide and metal chloride of Co+2, Ni+2, and Zn+2 ions in absolute ethanol. The present complexes are also characterized by techniques such as C.H.N, UV-vis, FTIR, TGA, molar conductivity, atomic absorption, and magnetic moment measurements. The in vitro antimicrobial activity of the prepared compounds was tested against two Gram-positive bacteria (Staphylococcus aureus and Bacillus) and two Gram-negative bacteria (Escherichia coli and Pseudomonas aeruginosa), as well as Candida albicans as a fungal species, by diffusion technique in addition to antioxidant properties. The spectroscopy measurement showed that the ligand coordinated with the metal ion as a tetradentate ligand via oxygen and nitrogen in addition to the chloride ion to form octahedral shapes. All compounds under study had a positive effect against antibacterial, antifungal, and antioxidant activities.